Microscopic characteristics of water invasion and residual gas distribution in carbonate gas reservoirs. Issue 11 (7th September 2021) - Chen, Pengyu; Liu, Huiqing; Zhao, Hailong; Guo, Chunqiu; Xing, Yuzhong; Cheng, Muwei; Shi, Haidong; Zhang, Liangjie; Li, Yunzhu; Su, Penghui
Abstract: We used the nuclear magnetic resonance online detection method to analyze the water invasion mechanism and residual gas distribution of a carbonate rock gas reservoir. The T2 spectra obtained by using the Carr‐Purcell‐Meiboom‐Gill (CPMG) pulse sequence were applied to characterize the invasion water and residual gas distribution. The results showed that (a) in the pore‐type gas reservoir, the water first invades the meso–macropores and then the small pores as the pressure decreases further. The fracture distribution in a fracture‐pore‐type gas reservoir has an effect on the water invasion mode. The water can enter the pores through the fracture wall after the water invades the fracture. (b) In the pore‐type gas reservoir, 37.7% of the residual gas resides in the small pores, while the rest resides in the macropores. While in the fracture‐pore‐type gas reservoir, 4.8% ~ 26.8% of the residual gas is in the smaller pores and 69.2% ~ 95.7% in the macropores. Barely, any residual gas resides in the fractures. The residual gas in the small pores is difficult to produce. (c) The residual gas is controlled by the fracture penetration, amount of bottom water, fracture width, and production rate. It is suggested the production rate decreased to induce the water to invade the meso–macropores after the gas well begins to produce water to reduce the amount of residual gas in the meso–macropores. Abstract : The nuclear magnetic resonance online detection method was used to analyze the water invasion mechanism and residual gas distribution of a carbonate rock gas reservoir, and theT2 spectra were obtained by using the Carr‐Purcell‐Meiboom‐Gill (CPMG) pulse sequence to characterize the intrusive water distribution